Analysis of simplified CCHP users and energy-matching relations between system provision and user demands. (April 2019) - Feng, Lejun; Dai, Xiaoye; Mo, Junrong; Shi, Lin
Highlights: Load demands of users were simplified and its mathematical models were established. Dimensionless load matching parameters and matching map were proposed. 53 types matching relations were established based on two capacity design modes. Effect of the load and time-related parameters to matching relations were discussed. Two capacity design modes for the three categories of CCHP users were compared. Abstract: Albeit numerous studies discussing manifold issues of combined cooling, heating and power (CCHP) systems, theoretical studies are still lack to indicate the energy-matching relations between system provision and user demands, and deficiency of research quantifying the influence of the key equipment capacities to energy saving rate (ESR) of systems. Therefore, in this research, theoretical discussions have been undertaken about the energy-matching relations. Comprehensive mathematical models of the load demands of users are established based on the simplified square wave demands, and three categories CCHP users are categorised based on the time-related parameters. Subsequently, according to the proposed dimensionless load-matching parameters, a load-matching map is drawn and 53 types load-matching relations for the three categories users are constructed based on two different capacity design methods. The research results indicate that "priority to providing electricity" method is a better choice to design the capacity of the CCHP systems for most load-matching relations and the users with smaller ratio of "mount load" to "valley load" and shorter synchronisation difference time between electricity and thermal energy will contribute higher ESR of CCHP systems.